Legends about “Jangar” in the national self-consciousness of the Kalmyks - M. U. Monraev (Nomadic Civilization: Historical Research)
The Oirats, after moving to the borders of Russia, to the Lower Volga, managed to preserve their epic “Dzhangar”. The key role in this was played by the dzhangarchi, the performers of heroic songs, who traditionally enjoy great respect among the Kalmyks. The article is devoted to a detailed textual analysis of the legends about the heroes of the Kalmyk heroic epic “Dzhangar”, recorded at different times by Russian researchers, as well as creatively reproduced in the works of national authors. The author for the first time introduces into scientific circulation the legend about the miraculous rescue of fishermen by the heroes of the epic, heard from his father. The legends he considered preserved the phraseology and intonations of the epic. The content of the legends is not directly related to the plots of the epic, there are separate episodes inspired by the spirit of the heroic epic of the Kalmyks. The artistic structure, the whole style of oral stories about “Dzhangar” fully correspond to the legend genre. Comparison of the plot of the legend, heard by the author from his father, with the previously known plots of legends about the origin of the national heroic epos, the receipt of the storytelling gift by its performers — dzhangarchi, allows us to conclude that its storyline is original, as well as artistic and visual means. A comparative analysis of the legends about “Dzhangar”, existing in the national selfconsciousness of the Kalmyks, is the subject of this article.